Effects of valence, geometry and electronic correlations on transport in transition metal benzene sandwich molecules. (8th September 2016) - Karolak, M; Jacob, D
Abstract: We study the impact of the valence and the geometry on the electronic structure and transport properties of different transition metal-benzene sandwich molecules bridging the tips of a Cu nanocontact. Our density-functional calculations show that the electronic transport properties of the molecules depend strongly on the molecular geometry which can be controlled by the nanocontact tips. Depending on the valence of the transition metal center certain molecules can be tuned in and out of half-metallic behaviour facilitating potential spintronics applications. We also discuss our results in the framework of an Anderson impurity model, indicating cases where the inclusion of local correlations alters the ground state qualitatively. For Co and V centered molecules we find indications of an orbital Kondo effect.